Effectiveness of Steamed Brownies Base on Fermented Black Glutinous Rice on Decreased Waist Circumference in Abdominal Obesity - Roro Nur Fauziyah; Mimin Aminah; Osman Syarief; Holil M Par’i; Widi Hastuti; Surmita Surmita (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Consumption of fiber and anthocyanins can decrease waist circumference and weight by lowering body fat levels. Steamed brownies base on fermented black glutinous rice is one of the cereals with high antioxidants, bioactive compounds, and fiber. The purpose of this research is to determine the effect of the effectiveness of steamed brownies based on fermented black glutinous rice on decreased waist circumference in abdominal obesity. The design of this research was experimental using two groups pre and post-test with control experimental design. The population in this research was adult women (35-50 years) in Pasirkaliki Village, North Cimahi Subdistrict, Cimahi City, with 40 samples. The intervention group was given steamed brownies base on fermented black glutinous rice, one puck (30 grams), and low-calorie diet education. The control group was given a low-calorie diet education. Statistical tests with the Wilcoxon Sign Rank test showed that there was a significant difference in waist circumference decreased at the beginning and the end of the research with p-value <0,001. Mann-Whitney test showed that there was an effect in steamed brownies base on fermented black glutinous rice giving to decrease waist circumference with p-value < 0,001. Steamed brownies base on fermented black glutinous rice can be as an alternative food for decreasing waist circumference.